Úvahy k výuce "historie" nejen na českých vysokých školách: Reflections on the teaching of "history" at Czech universities and elsewhere - Himl, Pavel (Dějiny – teorie – kritika, 2023)
The traditional idea of a single unified History has an impact not only on its basic working concepts (progress in a definite direction, important centre — unimportant peripheries, "significance" perceived from the point of view of politically influential groups and formations) and the way is written. A single History is also often reflected in a single Historiography, i.e. in a relatively unified and centrally organised institutional mechanism, that "produces" history. These mechanisms, most clearly to be seen in the higher educational system, basically continually reproduce the frontiers and models of "national historiography" as it emerged at the end of the 19th century. Discussion of alternative approaches to the writing of history and the forms of history teaching may on the one hand represent no more than "fights over territory" within the existing disposition of forces, but they may, on the other hand, help to loosening up of ideas of a single History and its single permissible interpretations.